2018
DOI: 10.3390/data3020019
|View full text |Cite
|
Sign up to set email alerts
|

UAT ADS-B Data Anomalies and the Effect of Flight Parameters on Dropout Occurrences

Abstract: An analysis of the performance of automatic dependent surveillance-broadcast (ADS-B) data received from the Grand Forks, North Dakota International Airport was carried out in this study. The purpose was to understand the vulnerabilities of the universal access transceiver (UAT) ADS-B system and recognize the effects on present and future air traffic control (ATC) operation. The Federal Aviation Administration (FAA) mandated all the general aviation aircraft to be equipped with ADS-B. The aircraft flying within… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Although adequate performance standards were established for various surveillance equipment, to date the impacts of surveillance system failures in terms of separation degradation, specifically in the UAS platform, have not been defined. Moreover, traditional radar and Mode-A/C transponder technologies show inherent deficiencies in different airspace and equipage scenarios especially in the presence of high air traffic densities [25][26][27][28][29][30][31][32][33]. The failure modes for different cooperative sensors such as Mode S, TCAS, ADS-B are well defined and safety assessments have been carried out on the individual surveillance sensor considering functions in the manned aircraft.…”
Section: Detect and Avoid (Daa) Safety Assessmentmentioning
confidence: 99%
“…Although adequate performance standards were established for various surveillance equipment, to date the impacts of surveillance system failures in terms of separation degradation, specifically in the UAS platform, have not been defined. Moreover, traditional radar and Mode-A/C transponder technologies show inherent deficiencies in different airspace and equipage scenarios especially in the presence of high air traffic densities [25][26][27][28][29][30][31][32][33]. The failure modes for different cooperative sensors such as Mode S, TCAS, ADS-B are well defined and safety assessments have been carried out on the individual surveillance sensor considering functions in the manned aircraft.…”
Section: Detect and Avoid (Daa) Safety Assessmentmentioning
confidence: 99%
“…A python module was developed to decode the archived data as defined in RTCA DO 282B [30]. The anomalies revealed in a step-by-step assessment can be divided into five distinct categories namely dropout, missing payload, low confidence data, data jump, and altitude discrepancy [15,16]. A summary of the ADS-B message evaluation is provided in Table 1 Table 1.…”
Section: Uat Ads-b Drop-outmentioning
confidence: 99%
“…As the onboard computer will make use of surveillance sensor data to trigger alert in the absence of the 'human eye', it is crucial to have robust and efficient surveillance sensors. However, studies have shown that, both the 1090ES and UAT ADS-B are prone to significant message degradations [8][9][10][11][12][13][14][15][16]. One of the drawbacks of ADS-B is message loss or dropout.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations